(untitled) - Chubb, Bruce A. (New York, 1997)
This will be the second edition of TAB's bestselling title on building your own universal computer interface. This edition will update the information on the step-by-step instructions for building a truly universal computer interface system (UCIS). The disk will contain all of the code needed to implement the hardware.
Keywords: Giao diện máy tính,Computer interfaces; Xây dựng và thiết kế,Design and construction